The Slovenian version of the oral health impact profile questionnaire (OHIP-SVN) : translation and psychometric properties - Rener-Sitar, Ksenija (Array, 2009)
Abstract: The aim of the study was to develop and to test the psychometric properties of the Slovenian version (OHIP-SVN) in the new cultural context. Construct validity was tested on 430 subjects, test-retest reliability on 60 subjects, internal consistency on 460 subjects, and responsiveness on 30 patients with a treatment demand (toothache). The significant association between the OHIP summary scores and the self-reported oral health (p<0.001) confirmed the construct validity. The test-retest reliability showed high intraclass correlation coefficients and no significant differences between the two administrations (p>0.05). The internal consistency showed high Cronbach’s alpha (0.97). The responsiveness was confirmed by the statistically significant difference between the mean OHIP score at baseline and follow-up (p<0.001) and by a considerable effect size in the patients with a treatment demand (0.515). The OHIP-SVN, as one of the first translation into one of the Slavic family of the languages proves that this instrument is suitable for the assessment of the Oral Health Related Quality of Life in Slovenia